Gamma Ray Irradiation for Crop Protection Against Salt Stress - Kumar, Pankaj; Sharma, Vasundhara; Yadav, Poonam; Singh, Bhupinder (Defence Life Science Journal, 2017)
Legumes have tremendous dietary value for human nutrition. However, the productivity of food legumes is always compromised owing to their insufficient ability to tolerate abiotic stresses such as drought or water logging, marginal soil, low/high temperatures and salt stress. Stress induces changes at the morphological, physiological, biochemical and molecular level which are consequently manifested in terms of reduced seed yield and quality. Salt stress is one of the most important constraints to crop production particularly in the arid and semi-arid regions of the world. Low dose of ionising radiation like gamma ray is reported to induce growth and several other physiological attributes in non-legume and legume crops. Relationship between seed gamma irradiation and salinity stress response could be related to favourable maintenance of gas exchange attributes (Pn, gs and E), 14C partitioning, activity of antioxidative enzymes (SOD, CAT and POX), membrane stability index (MSI) K+ to Na+ ratio, proline and glycine betaine content. One or more mechanisms may contribute simultaneously towards salt tolerance response of crop plants. The present review critically analyses the effect of gamma ray irradiation on growth and development of legumes under salt stress and evaluates the contribution of various physiological and biochemical mechanisms towards radiation mediated alleviation of salt stress response.